Global gradient estimates for non-quadratic vector-valued parabolic quasi-minimizers. (February 2015) - Habermann, J.
Abstract: We establish local and global higher integrability estimates for the gradient of vector-valued parabolic quasi-minimizers of integral functionals with polynomial p -growth, p > 2 n n + 2, on a parabolic domain Ω T in R n + 1, n ≥ 2 and under a weak regularity assumption on the parabolic boundary of Ω T .